MANAJEMEN INVENTARIS MELALUI DESAIN DATA PADA PENGRAJIN BENDA ROHANI KATOLIK - Hariwibowo, Ignatius; Sutarta, Agustinus Edi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service is carried out with the aim of helping to manage the inventory of goods for the craftsmen of Catholic spiritual objects. To achieve this goal, this service is carried out using an interview approach and system design analysis with a revenue and production cycle approach in accordance with the principles of the Accounting Information System. From the results of interviews and analysis, the creation of data designs will help entrepreneurs to be able to manage complex inventories. This data design will help the driver to be able to record the value of the inventory of goods used in assessing the cost of production. The result of this service is a data design that can be used for inventory data management to be able to determine the cost of production precisely. The design of this data is adjusted to the needs of craftsmen.